The first experimental seismic investigation over prospective uranium deposits at Mulga Rock, Western Australia - Urosevic, Milovan; Ziramov, Sasha; Moreau, X. (2016)
Mulga Rock area accommodates possibly one of the richest uranium deposits in the country and is situated in a remote part of Western Australia. Very soft, dry and unconsolidated near surface combined with a large size of the prospective territory require a non-standard approach to the application of geophysical methods. Considering also geological complexity of the area, high variability of the ore content as well as unknown stratigraphy below the current drilling depths that are not exceeding 200m, the geophysical method of choice for investigating such geological setting was reflection seismic. Our experimental survey involved several high resolution seismic lines over future test pits. Reflection profiles were helped by refraction tomography and MASW. The last two are to be utilised for geotechnical information for open pit mining. Reflection data utilised a "minimalistic" approach, but the resultant images are pleasing. Test pits below the lines will allow for a unique calibration but also ultimate evaluation of the seismic method.